ICT - Energy - Concepts Towards Zero Power Information and Communication Technology - Fagas, Giorgos; Gammaitoni, Luca; Paul, Douglas; Abadal Berini, Gabriel (IntechOpen, 2014)
A sustainable future for our information society relies on bridging the gap between the energy required to operate portable ICT devices with the energy available from portable/mobile sources. The only viable solution is attacking the gap from both sides, i.e. to reduce the amount of energy dissipated during computation and to improve the efficiency in energy harvesting technologies. This requires deeper and broader knowledge of fundamental processes and thorough understanding of how they apply to materials and engineering at the nanoscale, all the way up to the design of energy-efficient electronics. This textbook is a first attempt to discuss such concepts towards Zero-Power ICT. The content is accessible to advanced undergraduates and early year researchers fascinated by this topic. The book is realized through the EU-funded ZEROPOWER project.